2017
DOI: 10.21767/2171-6625.1000209
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Presentations and Factors Responsible for Delays in Diagnosis of Juvenile Myoclonic Epilepsy among Sudanese Patients

Abstract: Introduction: Juvenile Myoclonic Epilepsy (JME) is common idiopathic epilepsy manifested by myoclonic jerks that commonly noticed in early childhood without consciousness disturbance, then the generalised tonic -clonic overwhelms the scene, absence attacks are not uncommon. The prominent and cardinal EEG features of JME syndrome that supports the diagnosis is the generalized 3.5-6 Hz single, bifid and polyspikes slow-wave's complexes on normal brain background activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Patients with abnormal brain imaging, a history of severe head trauma, or an apparent neurological disability were excluded from the study, they were left with 2063 patients at the end. They found that the average age of Sudanese patients diagnosed with JME was 19.55 ±8.98 years, with a diagnostic delay of 4.35 years [2].…”
Section: Methods and Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Patients with abnormal brain imaging, a history of severe head trauma, or an apparent neurological disability were excluded from the study, they were left with 2063 patients at the end. They found that the average age of Sudanese patients diagnosed with JME was 19.55 ±8.98 years, with a diagnostic delay of 4.35 years [2].…”
Section: Methods and Resultsmentioning
confidence: 99%
“…The majority of articles reported myoclonic jerks as the first seizures type which are a hallmark of JME and are frequently overlooked or misdiagnosed as epileptic seizures by patients. Abdalla et al and Sharp et al reported that all patients experienced myoclonic jerks, with the upper limb bore bearing the highest percentage of jerks, followed by jerks over their entire body and lower limb jerks [2,4].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Mazumdar et al [4], presented three interesting cases of gaze palsy. Abdalla et al [5], evaluated the demographic features and the most common clinical presentations among the Sudanese individuals suffering from Juvenile Myoclonic Epilepsy (JME). Sin [6] presented a variant of Lemierre's syndrome, characterized by complete thrombosis of the left jugular vein.…”
mentioning
confidence: 99%
“…Juvenile Myoclonic Epilepsy (JME) is a generalized idiopathic epilepsy that manifests in the form of myoclonic jerks that are commonly observed during early childhood. Abdalla et al [5], evaluated the demographic features and the most common clinical presentations among the Sudanese JME patients. The results revealed that the mean age of individuals with JME at the time of diagnosis was 19.55 ± 8.98 years.…”
mentioning
confidence: 99%